Regenerative process evaluation of neuronal subclasses in chagasic patients with megacolon - Moreira, Milena D.; Brehmer, Axel; De Oliveira, Enio; Neto, Salustiano D.; Luquetti, Alejandro O.; Bueno, Lilian L.; Fujiwara, Ricardo T.; de Freitas, Michelle A.R.; Da Silveira, Alexandre B.M. (Human Immunology, 2013)
Chagas' disease is one of the most serious parasitic diseases of Latin America, with a social and economic impact far outweighing the combined effects of other parasitic diseases such as malaria, leishmaniasis and schistosomiasis. In the chronic phase of this disease, the destruction of enteric nervous system (ENS) components leads to megacolon development. Previous data presented that the regeneration tax in the ENS neurons is augmented in chagasic patients. Although, there are several neuronal types with different functions in the intestine a detailed study about the regeneration of every neuronal type was never performed before. Therefore, the aim of this study was to evaluate the regeneration tax of every neuronal cell type in the ENS from chagasic patients with megacolon and non-infected individuals. A neuronal regeneration marker (GAP-43) was used in combination with a pan-neuronal marker (Peripherin) and several neuropeptides markers (cChat, Substance P, NPY, VIP and NOS), and it was considered as positive just with the combination of these markers. Our results demonstrated that the regeneration levels of cChat, Substance P, and NPY were similar in chagasic patients and non-infected individuals. However, levels of VIP and NOS neuropeptides were increased in chagasic patients when compared with non-infected individuals. We believe that the augment in the regeneration occur due to an increased destruction of selective neuronal types. These results corroborates with previous studies that pointed out to selective destruction of VIP and NOS neurons in chagasic patients. © 2012 American Society for Histocompatibility and Immunogenetics.